No Heavenly Delusion? : a Comparative Study of Three Communal Movements. - Tyldesley, Michael (Studies in European Regional Cultures, 10., 2003)
"No Heavenly Delusion? analyses three movements of communal living, the Kibbutz, the Bruderhof and the Integrierte Gemeinde, all of which can trace their origins to the German Youth Movement of the first part of the twentieth century. The book looks at the alternative societies and economies the movements have created, their interactions with the wider world, and their redrawing of the boundaries of the public and private spheres of their members. The comparative approach taken allows a picture of dissimilarities and similarities to emerge that goes beyond merely obvious points of difference. Tyldesley places these movements in the context of intellectual trends in late nineteenth- and twentieth-century Europe and especially Germany, and enables the reader to evaluate their wider significance."--JSTOR website (viewed May 26, 2017).